Supervised Triple Macrosynchronized Lockstep (STMLS) Architecture for Multicore Processors - Pablo M. Aviles; Jose A. Belloch; Luis Entrena; Almudena Lindoso (IEEE Access, 2023)
In various fields, such as those with high-reliability requirements, there is a growing demand for high-performance microprocessors. Whereas commercial microprocessors offer a good trade-off between cost, size, and performance, they often need to be adapted to meet the reliability demands of safety-critical applications. To address this challenge, a Supervised Triple Macrosynchronized Lockstep architecture for multicore processors is presented in this work. Multiple recovery mechanisms, including rollback and roll-forward, have been implemented to harden the system. By integrating these mechanisms, the microprocessor becomes more robust and capable of mitigating potential errors or failures that may occur during operation. A quad-core ARM Cortex-A53 processor has been used as a case study, and an extensive fault injection campaign in the register file has been conducted to evaluate the effectiveness of our proposed approach. The results show that the hardened system exhibits high reliability, with 100% error coverage and error correction capabilities of up to 86.40%.